Management and Internal Standardization of Chemistry Terminology: A Northern Sotho Case Study - Taljard, Elsabé; Nchabeleng, Mahlodi Jean (Lexikos, 2011)
One of the many implications of the process of language democratization which started post-1994 in South Africa is the empowerment of the previously marginalized South African Bantu languages to become languages of higher functions, i.e. languages of learning and teaching, and also of scientific discourse. This in turn implies the development, consolidation and especially standardization of terminology for each of these languages, and the compilation of LSP dictionaries. This article describes the terminological processing of a technical source text prior to translation, which formed part of the compilation of a Quadrilingual Explanatory Dictionary of Chemistry. It reports on the model of terminology management that was utilized and explores strategies for the internal standardization of terms in the absence of readily available, standardized chemistry terminology.